2015
DOI: 10.1371/journal.pgen.1005228
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in RECQL Gene Are Associated with Predisposition to Breast Cancer

Abstract: The genetic cause for approximately 80% of familial breast cancer patients is unknown. Here, by sequencing the entire exomes of nine early-onset familial breast cancer patients without BRCA1/2 mutations (diagnosed with breast cancer at or before the age of 35) we found that two index cases carried a potentially deleterious mutation in the RECQL gene (RecQ helicase-like; chr12p12). Recent studies suggested that RECQL is involved in DNA double-strand break repair and it plays an important role in the maintenance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
96
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(103 citation statements)
references
References 21 publications
(20 reference statements)
6
96
0
1
Order By: Relevance
“…However, most of the breast cancer exome studies reported so far failed to discover genes, whose significance is similar to BRCA1, BRCA2, CHEK2, PALB2, etc. [19][20][21][22]25,28,[132][133][134][135][136]. For example, Snape et al [133] subjected to WES 50 patients with familial breast cancer; they composed the list of promising candidates, but did not communicate yet the results of subsequent case-control study or segregation analysis.…”
Section: Breast Cancermentioning
confidence: 99%
“…However, most of the breast cancer exome studies reported so far failed to discover genes, whose significance is similar to BRCA1, BRCA2, CHEK2, PALB2, etc. [19][20][21][22]25,28,[132][133][134][135][136]. For example, Snape et al [133] subjected to WES 50 patients with familial breast cancer; they composed the list of promising candidates, but did not communicate yet the results of subsequent case-control study or segregation analysis.…”
Section: Breast Cancermentioning
confidence: 99%
“…Candidate genes, such as those that encode proteins involved in the DNA damage response or DNA repair, have been identified by high throughput next generation sequencing and are being evaluated to determine their importance in cancer risk. Within the last month, Cybulski et al 4 and Sun et al 5 independently performed whole exome sequencing in breast cancer patients from distinct population groups and provided convincing evidence that mutations in the gene encoding the RECQL DNA helicase, a member of the conserved RecQ family of DNA helicases implicated in the maintenance of genomic stability, are associated with breast cancer susceptibility. recurrent RECQL breast cancer associated mutation (c.1667_1667C3delAGTA) was screened in over 13,000 breast cancer patients and 4,702 cancer-free individuals of Polish descent.…”
Section: Genetic Risk Factors For Breast Cancermentioning
confidence: 99%
“…5 A sequencing analysis of an additional 439 breast cancer patients revealed 9 RECQL germline mutations predicted to be pathogenic which included 3 nonsense mutations, one helicase domain-disruptive splice-site mutation, and 5 missense mutations in which the corresponding purified recombinant RECQL proteins were defective in helicase activity. Altogether, the pathogenic RECQL mutation frequency in the 448 familial breast cancer patients was 2.0% compared to 0.06% in 1,588 controls.…”
Section: Genetic Risk Factors For Breast Cancermentioning
confidence: 99%
See 2 more Smart Citations